Antioxidant Activity and Organoleptic Quality of Crackers with Differences in the Addition of Black Glutinous Tape and Baking Powder - Cahyaning Rini Utami; Nuriyah Fitriani (Journal of Natural Sciences and Learning, 2023)
Tapioca flour-based crackers are a popular dry snack in Indonesia, characterized by their high starch content. However, recent developments have focused on creating crackers that are not only tasty but also have high nutritional value. One way to achieve this is by fortifying crackers with fermented products like black glutinous rice tape. This ingredient is known for its excellent nutrition and high antioxidant content, making it a healthy addition to crackers. The expansion of the volume of crackers is the primary factor that affects the crispness and quality of the crackers. This study aims to determine the proportion of the addition of black glutinous rice tape and baking powder concentration to the characteristics of crackers and determine the best crackers that can produce good quality and are acceptable in terms of sensory. The research design was a randomized complete block design with two factors. The first factor of black glutinous rice tape percentage (20, 30, 40%) and the second factor of baking powder concentration (0.1, 0.2, 0.3%) repeated three times resulted in 27 attempts. The ANOVA two-way statistics was utilized by the researchers to evaluate the chemical data, followed by the Tukey test to detect any significant differences among the treatments. Moreover, they employed Friedman's method to carry out organoleptic testing. The Effectiveness Index method identified the best treatment for chemical and organoleptic analysis, which was T3B2 (0.2% baking powder and 40% black glutinous rice tape). This treatment resulted in an antioxidant activity of 141.15 ppm, a water content of 9.05%, and an ash content of 1.71%. In addition, the organoleptic scores for color, aroma, taste, and texture were rated 4.66, 4.66, 3.40, and 3.70, respectively (3=least liked, 4= liked).